Pengaruh Penerapan Akuntabilitas Keuangan, Pemanfaatan Teknologi Informasi, Kompetensi Aparatur Pemerintah Dan Ketaatan Peraturan Perundangan Terhadap Kinerja Instansi Pemerintah (Good Governance) Pada Organisasi Perangkat Daerah Kabupaten Bengkalis - Dariana Dariana; Annisa Meidyaroza Harrie (JAS (Jurnal Akuntansi Syariah), 2020)
This research aims to examine the effect of the application of financial accountability, utilization of information technology, the competence of government officials and compliance with laws and regulations on the performance of government agencies (good governance) partially and simultaneously in the organization of Bengkalis Regency. This research is a survey research with 160 respondents using a saturated sample method. The number of questionnaires returned was able to be processed as many as 130 respondents. This research uses multiple linear regression analysis models. The results of this research indicate that partially and simultaneously financial accountability, utilization of information technology, the competence of local government officials and obedience of laws and regulations have a significant effect on the performance of government agencies (good governance) in Bengkalis Regency regional apparatus organizations.